TUMBUHAN OBAT DAN KEARIFAN LOKAL MASYARAKAT DI SEKITAR KAWASAN TNBG, DESA SIBANGGOR JULU, KABUPATEN MANDAILING NATAL - Dwi Ratna Anjaning Kusuma Marpaung (Universitas Negeri Medan, 2018)
This study was conducted from April until June 2017 which aims to reveal the local wisdom in the utilization of medicinal plants by villagers of Sibanggor Julu, Mandailing Natal Regency. This study uses eksplorative survey method and Participatory Rural Appraisal method. Data were collected through semi-structure interviews with 37 infomants.based on the results of the interview can be seen that the community still believes with traditional medicine in life where obtained data that there are 31 types of medicinal plants classified into 2 classes are Monocotyledoneae with 5 families and Dicotyledoneae with 12 families. Zingiberaceae is the most dominant family in the utilization as medicinal plants and Kunyit or Curcuma longa L. is the type most widely used by villagers of Sibanggor Julu to treat the disease. Leaf was dominantly used as medicine by 39% and in the way of processing of medicinal plants is generally boiled by 28 %.